2020
DOI: 10.1111/ped.14272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of urachal remnants in children

Abstract: Background: This study aimed to evaluate the diagnosis and treatment of pediatric patients with urachal remnants. Methods: Medical records of patients diagnosed with urachal remnants between 2015-2019 were evaluated retrospectively. Age, gender, admission complaints, diagnosis, size of cysts, the complications that developed, and treatment modalities were recorded. Results: The study population consisted of 15 cases including seven girls. Most of the cases were asymptomatic. The urachal remnants were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
3
0
5
Order By: Relevance
“…Approximately one-third of the human urachus may not be completely occluded before birth and infancy, and still exist in adulthood ( 2 , 3 ). These embryological abnormalities include patent urachus, urachal cyst, urachal sinus, and vesicourachal diverticulum ( 4 ). Although usually asymptomatic, these remnants may cause infection, inflammation, fistulae, umbilical discharge, abdominal pain, or even, malignant transformation in the following years ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one-third of the human urachus may not be completely occluded before birth and infancy, and still exist in adulthood ( 2 , 3 ). These embryological abnormalities include patent urachus, urachal cyst, urachal sinus, and vesicourachal diverticulum ( 4 ). Although usually asymptomatic, these remnants may cause infection, inflammation, fistulae, umbilical discharge, abdominal pain, or even, malignant transformation in the following years ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study ironed out the previously published data demonstrated predominant incidence of UA in the younger patients with higher frequency among males. UA is often found incidentally on imaging, although in our case series, 100% of patients were symptomatic at the time of diagnosis and umbilical discharge was the most common presentation (64%) [11,12] . Additional complications of urachal anomalies such as progressive growth, stones, intracystic bleeding, intraperitoneal rupture, bowel stula, bowel obstruction, and malignancy are rare, as also we have observed in presented here study [12] .…”
Section: Discussionmentioning
confidence: 67%
“…Los remanentes uracales están presentes en el 1,6% de la población menor de 15 años y en el 0,6% de los adultos, con una prevalencia del 2% en la población general 5 , 6 . De acuerdo al lugar y extensión de la permeabilidad, puede originarse un uraco persistente (cuando existe una comunicación total entre ombligo y vejiga), un seno de uraco (si su apertura es únicamente en la zona umbilical), un divertículo uracal (si la permeabilidad se limita a la cúpula de la vejiga) o un quiste de uraco (cuando los dos extremos están obliterados con una dilatación quística entre estos) 7 . Un conducto uracal obliterado puede repermeabilizar después del nacimiento debido a diversas patologías que aumentan la presión intravesical.…”
Section: Discussionunclassified
“…Un conducto uracal obliterado puede repermeabilizar después del nacimiento debido a diversas patologías que aumentan la presión intravesical. El uraco persistente representa el 50% de estas anomalías, seguido por los quistes uracales (30%) 6 , 7 , que ocurren en 1 de cada 5.000 recién nacidos vivos con una razón hombre:mujer de 3:1, aunque solo tienen relevancia clínica en 1 de cada 150.000 casos pues a menudo son diagnosticados incidentalmente en personas asintomáticas 7 - 9 . La mayoría aparecen en el tercio inferior del uraco debido a la degeneración y descamación del epitelio transicional, y en su interior pueden proliferar bacterias e infectarse.…”
Section: Discussionunclassified
See 1 more Smart Citation